CORRELATION BETWEEN PROTHROMBIN TIME LEVELS OBTAINED USING PROTHROMBIN METER WITH LABORATORY IN NEONATES - Usman Shakil (Army Medical College Rawalpindi, 2019)
Objective: To determine correlation between the Prothrombin time obtained by Prothrombin time meter with Prothrombin time estimation by clinical laboratory in neonates.